Enhancing the performance of a BBDB using sloshing tanks (Proceedings of the European Wave and Tidal Energy Conference, 2025)
This work investigates the potential of improving the performance of a Backward Bent Duct Buoy (BBDB) wave energy converter by integrating sloshing tanks into its structure. A frequency-domain model is developed to couple the hydrodynamic response of the BBDB with additional pitch moments generated by sloshing, which are computed using Smoothed Particle Hydrodynamics (SPH) simulations with DualSPHysics. The influence of four tank geometries is assessed, focusing on how their dynamic behaviour interacts with the BBDB’s peak energy absorption frequency. Results show that the linearised model is valid for small pitch angles, and a particle spacing of dp=0.004m provides sufficient resolution for accurate simulation of the sloshing response. When the sloshing resonance matches the BBDB’s response period, energy capture is significantly enhanced achieving a maximum 40% increase in Capture Width Ratio. However, this improvement is frequency-dependent and not guaranteed for all configurations. Larger pitch amplitudes did not always translate into better performance.